Gremo v senco - Razpet, Nada (Fizika v šoli, 2016)
The observation of shadows is undoubtedly multi-layered and can be presented in a way that children in kindergartens, pupils in primary schools, and students of secondary schools and universities find interesting. The paper points out what we should be paying attention to when observing and drawing shadows with pupils in the last three grades of primary school.
Keywords: merjenja; poučevanje fizike; senca